Effects of nano-silica on the gas permeability, durability and mechanical properties of high-strength lightweight concrete. (30th August 2017) - Atmaca, Nihat; Abbas, Mohammed Layth; Atmaca, Adem
Highlights: Lightweight coarse aggregate (LWA) has been produced by pelletization technique. LWA has been replaced with coarse natural aggregate at different levels. The negative properties of LWAs can be remedied by the addition of nS particles. nS particles give better performance results in conventional concretes than LWCs. The durability of HSLWCs has been improved significantly by using nS particles. Abstract: This study presents an experimental investigation on the effect of nano-silica (nS) on the gas permeability, durability and mechanical properties of high strength lightweight concrete (HSLWC). In order to expose the effects of nS on the performance of concrete, the lightweight coarse aggregate (LWA) has been fabricated through cold bonded method by the pelletization process by mixing 10% of cement with 90% of fly ash (FA). Then, the utilization of HSLWCs has been finished off by volumetric substitution of normal coarse aggregate with 5 different levels, namely (0%, 10%, 20%, 30% and 40%) with and without nS at a constant water/binder ratio of 0.35 and a constant ratio of 20% of FA. The concrete has been tested at the age of 28 and 90 days for splitting tensile strength, sorptivity index, gas permeability and compressive strength as well as 3 and 7 days for compressive strength. It has been observed that the increase in the replacement of lightweight coarse aggregate affecting the strength and permeability properties negatively. On the other hand, the results indicate that the addition of 3% nS to HSLWCs reduce the negative properties of lightweight coarse aggregate and leads to remarkable increase in mechanical properties while the sorptivity and gas permeability values have been decreased up to 25% and 40% respectively, when the values compared with the same replacement levels of LWAs. Moreover, it has been found that nS particles have better results on normal concrete compared to the LWCs.